World School Life Versus Habitus: The breeding ground of an Educational Backward Mexico Migrant - Yurén, Teresa; de la Cruz, Miriam; Cruz, Alfonso; Araújo-Oliveray, S. Stella; Estrada, Marcos J. (Education Policy Analysis Archives, 2005)
In this article, three topics are interrelated: school desertion, poverty and migration. The situation in Mexico with respect to desertion and the relationship between this and several factors associated with poverty is presented. It is argued that scholastic desertion has an expanding effect which depends on the concurrence of two factors: disenchantment with schools and the "habitus" people adopt in cases of extreme poverty to assure their survival. In regard to the first of these factors, the normal course of schooling (the methods and the programs that are preferred in school) is critically analyzed and other indications that scholastic education is changing are examined. In regard to the second of these factors, the case of migrant Mexicans who go to the United States is examined. The results of a survey in Mexican junior high schools are reported and exploratory interviews were conducted with migrating Mexicans. The conclusions of other research carried out in Mexico dealing with scholastic desertion are also reconsidered.